2014
DOI: 10.1097/mcp.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to asbestos

Abstract: Although there is an expectance of decline in ARDs caused by industrial exposure to asbestos, the environmental exposure to asbestos is still a challenge waiting to be overcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Various investigators reported that this uncertainty is based upon the possibility that not all forms of asbestos drive an autoimmune response, and that autoimmune responses are seen more often with amphibole, rather than chrysotile, exposures (Ferro, et al 2013;Pfau, et al 2015;Pfau 2017). Historically, chrysotile exposures have been prevalent due to extensive commercial use, but reductions in asbestos mining and product manufacturing are revealing that environmental asbestos exposures are abundant, often contain amphibole fibers, and exert adverse health impacts even at low levels of exposure (Baumann et al 2013;Wolfe, et al 2017;Bayram and Bakan 2014, Buck, et al 2013, Lockey, et al 2015, Andujar et al, 2016Lemen, 2016;Szeinuk, et al 2017). Therefore, the current study regarding LAA suggests that more research is needed regarding specific mineral fibers that may be triggers for SAID.…”
Section: Introductionmentioning
confidence: 93%
“…Various investigators reported that this uncertainty is based upon the possibility that not all forms of asbestos drive an autoimmune response, and that autoimmune responses are seen more often with amphibole, rather than chrysotile, exposures (Ferro, et al 2013;Pfau, et al 2015;Pfau 2017). Historically, chrysotile exposures have been prevalent due to extensive commercial use, but reductions in asbestos mining and product manufacturing are revealing that environmental asbestos exposures are abundant, often contain amphibole fibers, and exert adverse health impacts even at low levels of exposure (Baumann et al 2013;Wolfe, et al 2017;Bayram and Bakan 2014, Buck, et al 2013, Lockey, et al 2015, Andujar et al, 2016Lemen, 2016;Szeinuk, et al 2017). Therefore, the current study regarding LAA suggests that more research is needed regarding specific mineral fibers that may be triggers for SAID.…”
Section: Introductionmentioning
confidence: 93%
“…In urban areas and in the Colombian Andean and Caribbean regions, the highest frequency among people attended by asbestosis were estimated in the two five-year periods and analyzed. Likewise, in these geopolitical regions are the cities with the highest demographic and industrial growth—factors that stimulated internal migration to main cities and influenced the level of urbanization [ 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between asbestos and lung cancer is still debated, 10 given the typically multi-factorial etiology of this cancer, whereas the causal relationship between asbestos exposure and mesothelioma is much more specific. 11 …”
Section: Discussionmentioning
confidence: 99%